Influence of the substituent D/A at the 1, 2, 3-triazole ring on novel terpyridine derivatives: synthesis and properties. Issue 29 (28th May 2019) - Zych, Dawid; Slodek, Aneta; Zimny, Dżastin; Golba, Sylwia; Malarz, Katarzyna; Mrozek-Wilczkiewicz, Anna
Abstract : The change in the substituents (D/A) at the 1, 2, 3-triazole ring of terpyridine derivatives shows a strong influence on the photophysical and biological properties of these derivatives. Abstract : In this study, we newly designed and developed a synthesis route based on the 1, 3-dipolar cycloaddition of the derivatives of 4′-(1, 2, 3-triazol-4-yl)phenyl-2, 2′:6′, 2′′-terpyridine with various (hetero)aryl substituents, differing in electronic character, on a triazol ring. The obtained compounds were comprehensively characterized by UV-Vis spectroscopy and electrochemical and thermal studies. Moreover, preliminary biological tests were conducted. The investigation allowed the selection of materials with the most promising properties with particular emphasis on the nature of the substituents. In addition, theoretical studies (DFT and TD-DFT) were performed to verify the comprehensive understanding of experimental results.